Ex-Dividend Date: Problematic Abnormal Returns for Sharia Stock Index Companies - Abdi Asmo; Adol Bastian; Neng Kamarni (DPPM Universitas Pelita Bangsa, 2024)
This research aims to determine changes in stock prices before and after the ex-dividend date at PT. Indonesian Sharia Bank. Tbk. This research uses a quantitative approach with the event study method to analyze stock fluctuations in an event. Whether or not stock fluctuations are present, data will be collected 30 working days before the event and 30 days after the event by means of a sample t-test. The test results show that the value of Sig. (2-tailed) of 0.042 <0.05, thus rejecting H0 and accepting H1 which means there is a difference in stock price fluctuations before and after the announcement of the ex-dividend date. The magnitude of the value of changes in stock prices with the value of dividends per share distributed has the conclusion that the magnitude of changes in stock prices is reflected in the magnitude of the value of dividends per share distributed by the company.